Studi Kelayakan Pengembangan Aplikasi Maximom Menggunakan Cost-Benefit Analysis pada Startup Maximom - Azura, Wahyu Novia Izza; Nurcahyawati, Vivine; Sutomo, Erwin (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2020)
The use of information technology at Maximom is an important component to support company operations. But in the planning and development of technology, it requires huge costs. On the other hand, Maximom is a new startup that does not yet have wide customer coverage and big capital. The feasibility study of Maximom's application can be seen through the economic feasibility approach using the Cost-Benefit Analysis calculation method. In identifying and calculating IT development costs, the Use Case Point method is required. Meanwhile, to identify and calculate the benefits of IT development can be helped by the Generic Ranti IS / IT Business Value method. The results of the feasibility study are development of the Maximom’s application is not feasible even though the development investment has benefit ratio of 1.2 times greater than the costs. Because of the development investment has not yielded a minimum return of 5%, net benefits are worth less than the initial capital, and the payback period is the same as the economic life of the investment, 3 years. For consideration, avoid the condition of the percentage value of benefits that decreases is greater than the percentage value of costs, because it can risk the investment feasibility.